Pollen transfer in fragmented plant populations: insight from the pollen loads of pollinators and stigmas in a mass‐flowering species - Delmas, Chloé E. L. (Ecol Evol, 2016)
Pollinator and/or mate scarcity affects pollen transfer, with important ecological and evolutionary consequences for plant reproduction. However, the way in which the pollen loads transported by pollinators and deposited on stigmas are affected by pollination context has been little studied. We investigated the impacts of plant mate and visiting insect availabilities on pollen transport and receipt in a mass‐flowering and facultative autogamous shrub (Rhododendron ferrugineum). First, we recorded insect visits to R. ferrugineum in plant patches of diverse densities and sizes. Second, we analyzed the pollen loads transported by R. ferrugineum pollinators and deposited on stigmas of emasculated and intact flowers, in the same patches. Overall, pollinators (bumblebees) transported much larger pollen loads than the ones found on stigmas, and the pollen deposited on stigmas included a high proportion of conspecific pollen. However, comparing pollen loads of emasculated and intact flowers indicated that pollinators contributed only half the conspecific pollen present on the stigma. At low plant density, we found the highest visitation rate and the lowest proportion of conspecific pollen transported and deposited by pollinators. By contrast, at higher plant density and lower visitation rate, pollinators deposited larger proportion of conspecific pollen, although still far from sufficient to ensure that all the ovules were fertilized. Finally, self‐pollen completely buffered the detrimental effects on pollination of patch fragmentation and pollinator failure. Our results indicate that pollen loads from pollinators and emasculated flowers should be quantified for an accurate understanding of the relative impacts of pollinator and mate limitation on pollen transfer in facultative autogamous species.